Oscillation thresholds via the novel MBR method with application to oncolytic virotherapy - Buonomo, Bruno; Della Marca, Rossella; Rionero, Salvatore (Nonlinear Analysis: Modelling and Control, 2022)
Oncolytic virotherapy is a therapy for the treatment of malignant tumours. In some undesirable cases, the injection of viral particles can lead to stationary oscillations, thus preventing the full destruction of the tumour mass. We investigate the oscillation thresholds in a model for the dynamics of a tumour under treatment with an oncolytic virus. To this aim, we employ the minimum bifurcation roots (MBR) method, which is a novel approach to determine the existence and location of Hopf bifurcations. The application to oncolytic virotherapy confirms how this approach may be more manageable than classical methods based on the Routh–Hurwitz criterion. In particular, the MBR method allows to explicitly identify a range of values in which the oscillation thresholds fall.